Recycling mechanisms and policy suggestions for spent electric vehicles' power battery -A case of Beijing. (10th June 2018) - Tang, Yanyan; Zhang, Qi; Li, Yaoming; Wang, Ge; Li, Yan
Abstract: In recent years, electric vehicles have developed rapidly in China, and recycling a large number of their spent power batteries will become a substantial challenge in the near future. However, the specific mechanisms and policies for recycling spent power batteries have still not been established in China. Therefore, the purpose of this study is to propose reward-penalty mechanisms and policies, and test their impacts on power battery recycling by using a Staklberg game theory based model. In the model, three single recycling channel modes and three competitive dual recycling channel modes were considered respectively. Furthermore, the total social welfare is used as the indicator to select the optimal recycling modes, which includes participants' profit, consumer surplus, government's supervision cost, energy-saving and carbon emission reduction effect. The obtained analysis results show that: (i) the intensive reward-penalty mechanism is more suitable for higher recycling rate modes, otherwise it may cause benefit losses, and thus, setting a reasonable minimum recycling rate as benchmark for reward-penalty mechanism is critically important; (ii) Environmental awareness has significant impacts on social benefits of power battery recycling; (iii) M&R (mode with competition between manufacturer and retailer in the recycling channels) has obvious advantages among these six recycling modes.